Development and application of a UHPLC-MS/MS method for the simultaneous determination of firmonertinib and its main metabolite AST-5902 in rat plasma: a study on the in vivo drug interaction between firmonertinib and paxlovid - Tang, Peng-Fei; Bao, Su-Su; Xie, Wei-Fei; Xiao, Zhong-Xiang; Wu, Xue-Meng; Ge, Hong-Lei (Frontiers in Pharmacology, 2025)
Due to the potential occurrence of drug interactions, the combined application of firmonertinib and paxlovid carries a relatively high risk. Nevertheless, as of now, there has been no comprehensive research on the interaction between firmonertinib and paxlovid. Our aim was to establish and validate an accurate, stable, rapid and simple UPLC-MS/MS method for the simultaneous determination of firmonertinib and its metabolite AST-5902 in rat plasma, which was applied to the study of the in vivo interaction between firmonertinib and paxlovid. Gefitinib was selected as the internal standard. After protein precipitation of the plasma samples with acetonitrile, the separation was carried out on a Shimadzu LC-20AT UHPLC. The chromatographic column was a Shim-pack Volex PFPP column (50 mm × 2.1 mm, 1.8 μm), and the mobile phase was composed of 0.1% formic acid - water and 0.1% formic acid - methanol. Mass spectrometry detection was performed using a Shimadzu 8,040 mass spectrometer in ESI+ and MRM mode. The precision, accuracy, recovery and matrix effect of this method were detected. The linearity of the method and the stability of the samples were assessed. Subsequently, the method was applied to the study of the interaction between firmonertinib and paxlovid. The parent ions and typical fragment ions of firmonertinib, AST-5902 and IS are respectively m/z 569.25 → 72.15, m/z 555.50 → 498.10 and m/z 447.25→ 128.20. The selectivity, specificity, linearity, recovery, matrix effect, accuracy and precision of the method and the stability of the samples were all adequately verified. The results of drug interaction showed that when firmonertinib was combined with paxlovid, the AUC and Cmax of firmonertinib were significantly increased, while the AUC, Tmax, and Cmax of AST-5902 were significantly decreased. The established UHPLC-MS/MS detection method is accurate, stable, rapid and simple. Paxlovid exhibit a significant inhibitory effect on the metabolism of firmonertinib in rats.